Traditional sheep and Goat production in southern Cote d'Ivoire - Armbruster, T.; Peters, Kurt J. (Elsevier, 1993)
The productivity performance of 34 traditional sheep and goat flocks in south-east Cote d'Ivoire were investigated. Average litter size was 1.19 lambs and 1.52 kids. Average annual lambing and kidding rate were 1.74 and 2.34, respectively. In both species, litter size was significantly influenced by age of dam and flock, and in goats, additionally, by grazing management. Ninety and 150-d weights of kids were significantly influenced by birth season, 90-d weight and sex. Sheep reached adult weight earlier than goats. Average 12- and 36-month weights of female were 17.9 and 22.6 kg for sheep and 12.5 and 19.3 kg for goats. Management, flock and season significantly influenced performance traits, which indicated improvement opportunities. The better performance of free-roaming flocks underlines the importance of sufficiently long daily grazing and browsing, while poor growth of lambs and kids born during rainy season indicated the necessity of improving flock health. Lamb and kid mortality up to 365 d of age was 48.1% in sheep and 44.2% in goats; average mortality in adults (>365 d old) was 20.9% and 23.3%, respectively. The economic analysis showed an annual return on capital investment of 27.8% in goat flocks and 27.2% in sheep flocks (labour cost of herding included).